Handbook of Manufacturing Systems and Design : An Industry 4. 0 Perspective. - Zaman, Uzair Khaleeq uz. (Taylor & Francis Group, 2023)
This handbook provides a comprehensive overview of manufacturing systems, their role in product/process design, and their interconnection with Industry 4.0 perspective, especially related to design, manufacturing, and operations.